What Explains Intra-Asian FDI Flows? Do Distance and Trade Matter? - Rajan, Ramkishen (2012)
This paper examines intra-Asian FDI flows using bilateral data over the period 1990 to 2005. Does the so-called distance puzzle that has characterized trade and FDI based gravity models exist in the case of intra-Asian FDI flows as well? And if so, to what extent can it be explained by informational assymetries and international trade as opposed to physical distance? These questions are explored in this paper.